Caracterización de la ansiedad en el adulto mayor - Moreno Romero, Carlos Fabricio (2020)
This case is based on a retired adult older than 72 years, who has been a victim of the impact caused by the pandemic that lives in the world in 2020, so that this patient has begun to present symptoms and behaviors due to the presence of a characterization of anxiety, which not only affects their physical and mental state but also negatively influences family and social life. In which work was carried out as a priority due to the vulnerability of the patient, in which the services of psychological tele-assistance were provided, which developed a psychotherapeutic process of 7 sessions which helped to determine a diagnosis and a focused therapeutic plan in cognitive behavioral therapy, since this therapy can be developed in a short period, and obtain short and positive results. This investigation was carried out under the parameters established by the government in which it was adapted to the new methodologies of attention for psychological first aid, in which it was possible to establish rapport and create a link between interviewer and interviewee, by joining the patient needs.